Was the Austrian agricultural policy least cost efficient? - Friedrich Schneider; Klaus Salhofer; Erwin Schmid; Gerhard Streicher (Johannes Kepler University of Linz, Department of Economics, 2001)
The study evaluates the efficiency of government intervention using a vertical structured model including imperfectly competitive agricultural input markets, the bread grain market, and the imperfectly competitive food industry. To test for policy efficiency the actually observed bread grain policy is compared to a hypothetical efficient policy. To account for the sensitivity of the results in regard to the model parameter values computer-intensive simulation procedures and surface response functions are utilized.
Keywords: Q18; D61; H21; 330; agricultural policy; efficient combination of policy instruments; statistical welfare analysis; Agrarmarktordnung; Getreidepolitik; Wirkungsanalyse; Wohlfahrtsanalyse; Österreich